2013
DOI: 10.5194/bg-10-81-2013
|View full text |Cite
|
Sign up to set email alerts
|

One year of continuous measurements constraining methane emissions from the Baltic Sea to the atmosphere using a ship of opportunity

Abstract: Abstract. Methane and carbon dioxide were measured with an autonomous and continuous running system on a ferry line crossing the Baltic Sea on a 2-3 day interval from the Mecklenburg Bight to the Gulf of Finland in 2010. Surface methane saturations show great seasonal differences in shallow regions like the Mecklenburg Bight (103-507 %) compared to deeper regions like the Gotland Basin (96-161 %). The influence of controlling parameters like temperature, wind, mixing depth and processes like upwelling, mixing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 59 publications
12
61
0
Order By: Relevance
“…504 nM and 1086 nM, respectively; Schmale et al, 2010). Compared to the atmospheric equilibrium, only slightly elevated methane concentrations (3-5 nM CH 4 ) prevail in the surface waters (Bange et al, 1994;Schmale et al, 2010;Gülzow et al, 2012). High-resolution gas chemistry studies in the water column of the Gotland basins showed a pronounced methane gradient and an enrichment of 13 C CH 4 within the pelagic redox zone that indicates microbial activity related to the aerobic oxidation of methane in that water depth .…”
Section: G Jakobs Et Al: Comparative Studies Of Pelagic Microbial Mmentioning
confidence: 98%
See 1 more Smart Citation
“…504 nM and 1086 nM, respectively; Schmale et al, 2010). Compared to the atmospheric equilibrium, only slightly elevated methane concentrations (3-5 nM CH 4 ) prevail in the surface waters (Bange et al, 1994;Schmale et al, 2010;Gülzow et al, 2012). High-resolution gas chemistry studies in the water column of the Gotland basins showed a pronounced methane gradient and an enrichment of 13 C CH 4 within the pelagic redox zone that indicates microbial activity related to the aerobic oxidation of methane in that water depth .…”
Section: G Jakobs Et Al: Comparative Studies Of Pelagic Microbial Mmentioning
confidence: 98%
“…This modified method includes the following process steps: the samples were stripped with helium to remove volatile constituents (purge step), dried using a Nafion ® trap (Perma Pure LLC., USA), cryofocussed at −120 • C (ethanol / nitrogen) on HayeSep D ® (Valco Instruments Company Inc., Switzerland) desorbed by heating at 85 • C and analyzed using a gas chromatograph (Shimadzu GC-2014) equipped with a flame ionization detector. The concentration of oxygen was determined by titration method (precision ± 0.9 µM O 2 ) and the hydrogen sulfide concentrations were measured calorimetrically using the methylene blue method (precision ± 1.0 µM H 2 S) (Grasshoff et al, 1999). Oxygen concentrations were only determined for samples virtually devoid of hydrogen sulfide.…”
Section: Methane Oxygen and Hydrogen Sulfidementioning
confidence: 99%
“…The recent development of sensitive analytical techniques based on infrared detection such as cavity ringdown spectroscopy (CRDS), enhanced integrated cavity output spectroscopy (ICOS) and off-axis integrated cavity output spectroscopy (OA-ICOS) has enabled the detection of a number of trace gases in nanomolar concentrations and opened the possibility of obtaining continuous measurements for a variety of applications, including soil and atmospheric monitoring (Baer et al, 2002;Kasyutich et al, 2003;Maddaloni et al, 2006) as well as for surveys of the surface ocean onboard research vessels (Becker et al, 2012;Grefe and Kaiser, 2013) and ships of opportunity (Gülzow et al, 2011(Gülzow et al, , 2013. This represents a great improvement compared to conventional detection techniques (mainly based upon gas chromatography) due to the strongly increased temporal resolution that can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the Baltic Sea, the methane flux from the deep methane pool toward the sea surface is strongly hampered by microbial methane oxidation within the oxic/anoxic transition zone below the permanent halocline (Berndmeyer et al ; Jakobs et al ; Schmale et al ). Continuous equilibrator measurements of the concentration of methane in the surface water conducted in the Baltic Sea indicate that the formation of a thermocline during the summer leads to a buildup of a methane pool below this upper density boundary (Gülzow et al ). The wind‐induced mixing of the water column during autumn and winter ventilates the accumulated methane upward resulting in elevated, though small, methane fluxes into the atmosphere in the central Baltic Sea (Gülzow et al ).…”
mentioning
confidence: 99%